Transition to Parenthood and Marital Satisfaction: A Meta-Analysis - Bogdan, Ionela; Turliuc, Maria Nicoleta; Candel, Octav Sorin (Frontiers in Psychology, 2022)
The transition to parenthood is a major life event characterized by profound changes for a considerable number of people. Previous meta-analyses summarized the results obtained by various researchers in the first year and, respectively, in the first 2 years postpartum, globally. The current study adds to the literature by testing the changes from 12 to 24 months, the cross-partner associations and the analysis of different moderators. The aims of this present meta-analysis are to investigate the decrease in marital satisfaction during the first and second year postpartum, to examine cross-partner associations of the decline in postpartum marital satisfaction, and to investigate the potential moderating variables of this decrease. Forty-nine studies (97 samples of parents and 9 samples of non-parents) that fit our criteria are included in the meta-analysis. The data analysis was performed using meta-analytic techniques. Marital satisfaction has a medium decrease between pregnancy and 12 months postpartum, and a small decline between 12 and 24 months postpartum for both genders. In a similar period with first year postpartum, non-parents present a small decline in marital satisfaction. Moreover, the analysis of the dyadic studies data shows cross-partner associations, confirming that one partner’s satisfaction has a steeper decline when the other partner’s satisfaction presents a steep decrease. The decrease in marital satisfaction does not stop after the first postpartum year, and the coss-partners associations are present. Theoretical and therapeutic implications are also discussed.